Dextran‐based hydrogel with enhanced mechanical performance via covalent and non‐covalent cross‐linking units carrying adipose‐derived stem cells toward vascularized bone tissue engineering. Issue 6 (13th March 2019) - Cai, Litao; Li, Jitian; Quan, Songtao; Feng, Wei; Yao, Junna; Yang, Minglu; Li, Wuyin
Abstract: Hydrogels for biomedical applications were limited toward bone tissue engineering due to the poor mechanical performance. Tough hydrogels with strong and elastic features have received extensive attention, the application of which, however, was limited by their degradation. The present study introduced an approach to enhance mechanical properties of hydrogel while ensuring its degradation. Carboxyl dextran (Dex) was grafting modified by poly (ε‐caprolactone) (PCL), sequentially followed by being cross‐linked through polyethyleneglycol 400 (PEG400) to yield a gel with covalent cross‐linking units in DMSO. The gel was underwent solvent displacement in H2 O to induce hydrophobic association of PCL to form non‐covalent cross‐linking units. The tough Dex‐g‐PCL hydrogel showed maximum strain of Dex‐g‐PCL hydrogel was 90% ± 6%, with the corresponding stress of 2.7 ± 0.2 MPa, which was significantly enhanced when comparing to dextran hydrogel (maximum strain 65% ± 5%, with the corresponding stress of 0.225 ± 0.06 MPa). Most hydrogel degraded after 12 w in vivo with only a little residues. Adipose‐derived stem cells (ASCs) proliferated well after being seeded in hydrogel to form micro‐mass at 14 days post‐seeding. In vitro and in vivo angiogenesis, as well as in vitro osteogenesis illustrated the potential of the Dex‐g‐PCL hydrogel carrying ASCs toward vascularized bone tissue engineering. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 1120–1131, 2019.